2017
DOI: 10.1016/j.neuropharm.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the first biased NPS receptor agonist that retains anxiolytic and memory promoting effects with reduced levels of locomotor stimulation

Abstract: The neuropeptide S system has been implicated in a number of centrally mediated behaviors including memory consolidation, anxiolysis, and increased locomotor activity. Characterization of these behaviors has been primarily accomplished using the endogenous 20AA peptide (NPS) that demonstrates relatively equal potency for the calcium mobilization and cAMP second messenger pathways at human and rodent NPS receptors. This study is the first to demonstrate that truncations of the NPS peptide provides small fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…This observation is compatible with a previous study in hippocampal mouse neurons (Erdmann et al, 2015). The NPS effects on intracellular Ca 2ϩ also studied in NPSR1-transfected HEK293T and CHO cells are most likely mediated by NPSR-induced G q signaling (Reinscheid et al, 2005;Liao et al, 2016;Clark et al, 2017). In vivo, it has recently been demonstrated that NPS promotes anxiolysis in a phospholipase C-dependent manner and increases intracellular Ca 2ϩ levels characterized by increased phosphorylation and synthesis of Ca 2ϩ /calmodulin-dependent kinase II within the rat medial amygdala (Grund and Neumann, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This observation is compatible with a previous study in hippocampal mouse neurons (Erdmann et al, 2015). The NPS effects on intracellular Ca 2ϩ also studied in NPSR1-transfected HEK293T and CHO cells are most likely mediated by NPSR-induced G q signaling (Reinscheid et al, 2005;Liao et al, 2016;Clark et al, 2017). In vivo, it has recently been demonstrated that NPS promotes anxiolysis in a phospholipase C-dependent manner and increases intracellular Ca 2ϩ levels characterized by increased phosphorylation and synthesis of Ca 2ϩ /calmodulin-dependent kinase II within the rat medial amygdala (Grund and Neumann, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a truncated version of the NPS peptide, called compound 4, has been demonstrated to evoke anxiolysis and to induce memory-promoting effects with reduced levels of locomotor stimulation following ICV infusion in mice (Clark et al, 2017). In HEK293T cells transfected with NPSR107I, compound 4 demonstrated a strong level of bias for the Ca 2+ mobilization pathway over the cAMP pathway (Clark et al, 2017), in line with our results demonstrating that a block of PLC signaling in the presence of NPS prevents its anxiolytic profile. Although NPS induces cAMP accumulation in HEK293T cells in vitro , a cAMP-independent mechanism seems to be involved in the anxiolytic effect of NPS in the MeA.…”
Section: Discussionsupporting
confidence: 83%
“…As reported for several GPCRs, the intracellular signaling cascade that follows NPSR activation is complex and involves different parallel pathways such as Gq, Gs, and extracellular signal‐regulated kinases (ERKs)). Additionally, the complexity of NPSR signaling has been recently underlined by the identification of NPSR biased agonists, such as NPS (1‐10) and SFKN‐NH 2, that preferentially signal through IP 3 ‐DAG‐Ca 2+ second messengers. This class of NPSR ligands may be useful as innovative anxiolytics .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the complexity of NPSR signaling has been recently underlined by the identification of NPSR biased agonists, such as NPS (1‐10) and SFKN‐NH 2, that preferentially signal through IP 3 ‐DAG‐Ca 2+ second messengers. This class of NPSR ligands may be useful as innovative anxiolytics . Despite this NPSR signaling complexity, structure‐activity relationship studies and drug discovery programs targeting NPSR have been conducted so far only with classical single end‐point assays (for reviews see and ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation